Air layering in nutmeg (Myristica fragrans Houtt.) - Nissar, V A M; Sasikumar, B; Rema, S Aarthi, J (Journal of Spices and Aromatic Crops, 2019)
Nutmeg is an important perennial spice crop, which is dioecious in nature. Vegetative propagation is the norm in commercial propagation of the tree. The existing practice of propagation is grafting and budding which needs good skill and expertise for reasonable success. As an alternative to these two methods, air layering was attempted in matured trees for the first time in the country. Air layering was successful in plagiotropic and orthotropic shoots with 100 per cent survival. This method is cost effective and is easy for adoption.